Improvement of E Se tea extracts on renal mesangial cell apoptosis and high-fat-diet/streptozotocin-induced diabetic nephropathy. (September 2021) - Tan, Meng; Fan, Chengde; Wang, Minzhu; Li, Xinyu; Yuan, Ruiying; Yang, Jing; Dongzhi, Zhuoma; Huang, Shan; Wang, Yuefei; Li, Bin
Graphical abstract: Highlights: E Se tea inhibited oxidative stress-induced mesangial cell apoptosis. E Se tea achieved the protective effects through mitochondrial/caspase pathway. E Se tea improved high-fat-diet/streptozotocin-induced diabetic nephropathy rats. E Se tea decreased activation of renal caspase 3 on diabetic nephropathy rat. Abstract: E Se tea, the leaves of Malus toringoides (Rehd.) Hughes, is a kind of traditional beverage, which is often used to relieve hyperglycemia and hyperlipidemia and other symptoms, while its effect on diabetic nephropathy (DN) is still unclear. In this study, we evaluated the improvement of the ethanol extract of M. toringoides (EMT) on tert-butyl hydroperoxide (t-BHP)-induced rat glomerular mesangial cells (HBZY-1) apoptosis and high-fat-diet (HFD)/streptozotocin (STZ)-induced DN rats. The results showed that the EMT significantly reversed apoptosis, mitochondrial depolarization and cysteinyl aspartate specific proteinase (caspase) 3/9 activation in t-BHP (50 μM)-exposed HBZY-1 cells. Moreover, 8-weeks treatment of EMT improved blood glucose, proteinuria, serum creatinine and urea nitrogen, renal oxidative stress, proinflammatory mediators, histopathology and decreased activation of caspase 3. These results suggested that the E Se tea may therefore be a potential complementary therapy targeting DN patients.